al-Tadrīs al-Fa‘āl li-Mahārat al-Muḥādathah li-al-Mustawá al-Mutaqaddim - Othman bin Musa Alsa’di (Al-Ma’rifah, 2018)
This research aims to present my experience in teaching the advanced level of conversational skills in the Sultan Qaboos College for teaching Arabic to other speakers using the effective teaching method to deal with questions such as: What will I do when I teach the advanced level of conversation and how will I study it? Will the topics be exciting for motivation in different classroom situations? Will the conversation be effective in the classroom and beyond? The study concluded with the importance of providing the participants in the teaching of Arabic to foreigners with practical experience, mechanisms, and interactive methods, and to fill some of the shortage in this field of knowledge and by following the descriptive-analytical approach. It also included the topics studied in this experiment. The most important conclusion: the importance of correct assessment of students before starting to teach the best way to success Effective teaching, patience is also necessary for successful linguistic production, in addition to motivation as well as the synergy of methods and principles of effective teaching all leads to the integration of the student gradually in the Leah classroom and with his colleagues and with the environment is not class later.